Analisis Penerapan Sistem Informasi Manajemen terhadap kinerja pegawai Usaha Daster Dasby’D - Veni Gerhana Putri; Anissa Aprilia Dewanti; Amin Sadiqin (CV ODIS, 2023)
This research entitled Analysis of the Application of Management Information Systems on the performance of Dasby'D Business employees was carried out to find out what it looks like and how the effect of implementing a management information system on the performance of Dasby'D employees. This research was conducted through a survey related to the use of management information systems on the performance of employees. Metode conducted observations and interviews with respondents (Dasby'D employees). Based on the results of the research conducted, a description is that if the management information system is implemented, it will significantly affect the performance of Dasby'D business employees. Based on qualitative data, a firm leader with good communication to implement an organized and good management information system can significantly affect the performance of employees. The results can know this of interviews and observations where state that they will feel enthusiastic about working if they have a boss who can give clear and appropriate directions and can provide support to employees so that employees can be motivated to work better later will also have a significant effect on the sales produced.